The Influence of Customer Experience, Customer Delight, and Perception, and on Online Shopping Customer Loyalty (Case Study on Students in Medan City) - Jeffany; Hendry Kosasih; Vinsen; Purnama Yanti Purba (Institute of Computer Science (IOCS), 2021)
This study aims to determine and analyze the influence of Customer Experience, Consumer Perception and Customer Delight on customer loyalty. The phenomenon of increasing online shopping during this pandemic and the suggestions of previous researchers are the background of this research. The research method used is Multiple Linear Regression Analysis. The type of research used is descriptive quantitative research and the nature of this research is explanatory research. Simple Random Sampling is used to determine the sample in this study. The population used is students in the city of Medan and the sample of this study was taken as many as 100 respondents. The results showed that Customer Experience partially had a positive and significant effect on Customer Loyalty, Consumer perception has no positive and significant effect on customer loyalty. customer delight has no significant effect on Customer Loyalty. In addition, simultaneously Customer Experience, Consumer Perception and Customer Delight have a positive and significant impact on Customer Loyalty